Biochemical and behavioral effects of decreasing dietary linoleic acid and increasing eicosapentaenoic acid and docosahexaenoic acid in a rat chronic monoarthrits model. (December 2022) - Domenichiello, Anthony F.; Wilhite, Breanne C.; Nara, Pranavi; Pitcher, Mark H.; Keyes, Gregory S.; Mannes, Andrew J.; Bushnell, M. Catherine; Ramsden, Christopher E.
Highlights: We fed rats a diet that was higher in omega 3 polyunsaturated fatty acids and low in linoleic acid, compared to the control diet designed to mimic US fatty acid intakes. Compared to rats fed the control diet, the H3L6 diet-fed rats had lower concentrations of linoleic acid, and oxidized lipids derived from linoleic acid, as well as higher concentrations of omega 3 polyunsaturated fatty acids, and omega 3 derived oxidized lipids. The H3L6 diet did not impact pain related behavior in a rat chronic monoarthritis model. Abstract: Clinical studies have demonstrated that decreasing linoleic acid (LA) while increasing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in diets evokes an analgesic effect in headache sufferers. We utilized a rat chronic monoarthritis model to determine if these analgesic effects can be reproduced in rats and to and further probe potential analgesic mechanisms. We fed 8 rats a control diet (with fatty acid levels similar to standard US diets) and 8 rats a low LA diet with added EPA and DHA (H3L6 diet) and after 10 weeks, performed a unilateral intraarticular injection of Complete's Freund Adjuvant (CFA). We evaluated thermal and mechanical sensitivity as well as hind paw weight bearing prior to and at 4 and 20 days post CFA injection. At 28 days post CFA injection rats were euthanized and tissue collected. H3L6 diet fed rats had higher concentrations of EPA and DHA, as well as higher concentrations of oxidized lipids derived from these fatty acids, in hind paw and plasma, compared to control fed rats. LA and oxidized LA metabolites were lower in the plasma and hind paw of H3L6 compared to control fed rats. Diet did not affect thermal or mechanical sensitivity, nor did it affect hind paw weight bearing. In conclusion, the H3L6 diet evoked biochemical changes in rats but did not impact pain related behavioral measures in this chronic monoarthritis model.